Analyzing structural relationships between service quality, disconfirmation, satisfaction and loyalty / Wei Mei Chin - Wei, Mei Chin (Accounting Research Institute (ARI), 2010)
This research aims to analyze the relationships between service quality, disconfirmation, satisfaction, and loyalty. A structured methodology combined with both models in overall evaluation (e.g. Fornall et al.) and disconfirmation(e.g. Oliver et al.) were used in order to capture the perceptions of satisfaciton. Customer satisfaction is widely used due to its importance to organizations, the measurement of customer satisfaction has its problems. Many scholars then started to research on this idea, today there is much ambiguous evidence in the worldwide journals. Early researchers considered satisfaction as antecedent factors that affect service quality, different opinions of causal relationship discussed in the past, that consider satisfaction generate service quality via word-of-mouth, service loyalty, later researchers, however, considered service quality as the important factor that affect satisfaction. Thus, how service quality is evaluated, what kind of value is perceived, whether the customer is satisfied with the product/service, and what is the intended behavior towards the purchase experience. In this study, basically we adopt the views of Oliver in service quality by expectation level and perceptions of disconfirmation and Czepiel and Fornell by considering customer satisfaction as a type of overall evaluations as a model of measurement.